Analisis Kemampuan Pemecahan Masalah Matematika Siswa Berbasis Jumping Task pada Materi Program Linear - Bernard, Bernard; Djam’an, Nurwati; Sari, Indah (Program of Mathematics Education Department of Mathematics Faculty of Mathematics and Natural Sciences (FMIPA) Universitas Negeri Makassar (UNM), 2024)
This research is a qualitative research using descriptive research method which aims to explain or describe students' mathematical problem solving abilities in solving questions based on jumping tasks based on students' self-efficacy. The subjects of this study were 3 (three) students from class XI. Data collection techniques in this study were tests, questionnaires and interviews. The instruments used to obtain data were self-efficacy questionnaires, test questions (jumping task-based math problems), and interview guidelines. Data analysis techniques in this study include data condensation, data presentation, and drawing conclusions. The results of this study indicate that: (1) students who have high self-efficacy are able to fulfill the four stages of Polya's problem solving so that their problem solving abilities are high.; (2) students who have moderate self-efficacy are only able to fulfill three stages of Polya's problem solving so that their problem-solving abilities are classified as moderate; (3) students who have low self-efficacy are only able to fulfills one stage of Polya's problem solving so that the problem solving ability is low